Experiences of Patients with Covid-19 from Home Care: A Qualitative Study - Yekefallah, Leili; Mohammadi, Sareh; Ahmadi, Abbas (Advances in Nursing & Midwifery, 2023)
Introduction: The demand for home care services has increased not only due to the increase in the elderly population but also due to consumer preference and technological advances that allow for the provision of sophisticated home care. Home healthcare services aim to help people improve their performance and live a more independent life, improve their well-being, and help them stay home, avoiding hospitalization. This study aimed to study the Experiences of patients with COVID-19 from home care in Qazvin City. Methods: A qualitative study with a conventional content analysis method was used. Ten participants were selected using purposeful sampling from 5 October to 25 May 2020. In‐depth structured interviews were used to collect data. Data were analyzed by continuous comparative analysis using MAXQDA 10 software. Results: Data analysis on patients’ experiences with COVID‐19 specified twelve mean units, eight subthemes, and four themes, including Economic, Emotional, Reliability, and Support. Conclusions: All patients have common experiences in the fields of Economic, Emotional, Reliability, and Support. In future waves of COVID‐19, or a new pandemic, home care holds the potential to serve as a source of overflow care when acute care settings are overburdened and patients are discharged from acute and long‐term care settings.